Hubungan Harga Diri dengan Tingkat Stres Akademik pada Mahasiswa - Amanda Putri; Betie Febriana; Wahyu Endang (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Academic stress is a common type of stress experienced by students, which greatly affects their self-esteem. This study aims to determine the relationship between self-esteem and academic stress levels among students. This study used a quantitative design with a cross-sectional approach and probability sampling technique. The sample consisted of 101 respondents from a total of 132 students. Data analysis was performed using Spearman's rank correlation test. The results showed a weak and negative relationship between self-esteem and academic stress levels with a p-value of 0.000 (p˂ 0.05) and a correlation coefficient (r) = -0.385. There is a relationship between self-esteem and academic stress levels in students, where low self-esteem is associated with higher academic stress levels.